Capsule endoscopy in inflammatory bowel disease type unclassified and indeterminate colitis serologically negative - Lopes, S (2016)
BACKGROUND: The value of capsule endoscopy in the setting of inflammatory bowel disease type unclassified (IBDU) and indeterminate colitis (IC) remains obscure. The aim was to evaluate the clinical impact of capsule endoscopy on IBDU/IC patients with negative serology. METHODS: Eighteen patients with long-standing IBDU (n = 14) and IC (n = 4) were enrolled to undergo a capsule endoscopy and then followed prospectively. Lesions considered diagnostic of Crohn's disease (CD) were 4 or more erosions/ulcers and/or a stricture. The median follow-up time after capsule endoscopy was 32 ± 11 months (23-54 months). RESULTS: Total enteroscopy was possible in all patients. In 2 patients the examination was normal (Group 1). In 9 patients subtle findings were observed (Group 2): focal villi denudation (n = 1) and fewer than 4 erosions/ulcers (n = 8). In 7 patients, 4 or more erosions/ulcers were detected (Group 3), leading to a diagnosis of CD. However, their treatment was not reassessed on the basis of the capsule findings. Until now, a definitive diagnosis has been achieved in 2 additional patients: 1 from Group 1 (ulcerative colitis) and another patient from Group 2 (CD), who began infliximab infusions. Nine patients remained indeterminate at follow-up. CONCLUSIONS: Although capsule endoscopy enabled the diagnosis of CD in 7 patients, in none of them was the clinical management changed. Moreover, a change in therapy due to a diagnosis of CD was made for only 1 patient, who presented nonspecific findings. Our results suggest that capsule findings are not helpful in the work-up of these patients